Analisis dampak ENSO terhadap debit aliran DAS Cisangkuy Jawa Barat menggunakan model Rainfall-Runoff - Yopi Ilhamsyah (Depik, 2012)
Abstract. A study of analysis of ENSO impact on streamflow of Cisangkuy watershed West Java using Rainfall-Runoff model was done. The study was analyzed by using GR4J model. Daily rainfall and potential evaporation are model initial data. The model was tested for 2 years running by applying least square error method provided by spreadsheet application to reduce the initial value problem. The model showed a good result with Nash-Sutcliffe Efficiency of 70.0. The model was then simulated for 5 years. Monthly streamflow which is model output was then analyzed. The ENSO impact was done by identifying SOI to the variability of rainfall and streamflow. The model result showed that during La-Niña year in 2000, streamflow decreased below normal. The situation remain question that need to be further investigated. During normal year from 2001 to 2004, streamflow was normal. However, during El-Niño year, the decreasing rainfall also have an effect on the decreasing of streamflow in Cisangkuy watershed. The result also showed that the correlation between climate anomaly Nino 3.4 and variability of rainfall and streamflow is significant with correlation coefficient of -0.69 and -0.30, respectively. The regression model was governed and was then utilized to predict the risk analysis in Cisangkuy watershed by using stochastic spreadsheet under Crystal Ball application.